П. М. Федченко. Михайло Драгоманов: життя і творчість - Мельник, В. Я.; Комзюк, Л. Т. (Український історичний журнал, 2025)
П. М. Федченко. Михайло Драгоманов: життя і творчість. К.: Дніпро, 1991. — 562 с